Mastering Computer Linguistics for the Designation of Risks in Cooperation Communications - N. Vnukova; S. Hlibko; D. Davydenko; V. Shorokh (My University, 2022)
Google Trends is a popular computational linguistics tool designed to determine and analyze the range of public interests, taking into account the linguistic features of the formation of Internet queries. In this paper, it is proposed to use the Google Trends service to determine the risks of cooperative ties between industrial enterprises of the Kharkiv and Zaporizhia regions, which are already leaders in industry clustering in Ukraine. The information base of the study was the groups of enterprises, which were determined by the analysis of the hierarchy of cooperation relations. An analysis of the names of enterprises in the group using Google Trends made it possible to determine the demand for their products by region, which made it possible to assess the state of their promising cooperation. In this aspect, a list of clustering risks is defined, a relative assessment of indicators according to the linguistic features of the formation of scales including. The work carried out an experiment with Kharkіv enterprises, which made it possible to make a decision on cooperation with certain institutions, taking into account the processing of qualitative indicators by using linguistic information. Thus, the scientific novelty of the paper is the technology of processing quality information with widespread use of methods of using linguistic information, which is important for the formation of prerequisites for decision-making in economics was developed by the authors.
Keywords: Computational Linguistics; Google Trends; Risk of Cooperation; Matrix; Interaction; Partnership